Morphometric and Biochemical Analysis with Seed Protein Profiling of Passiflora Species Found in the Northeastern Himalayan Region of India - Kripa Shankar; Senjam Romen Singh; Lobsang Wangchu; Arunkumar Phurailatpam; Lukram Shantikumar; Ps. Mariam Anal; Nongthombam Devachandra; Budhindra Nath Hazarika; Aria Dolatabadian (Horticulturae, 2025)
Passion fruit is an underutilised fruit in Northeastern India, known for its unique flavour and health benefits. This study analysed 15 genotypes (P1 to P15) to explore their morphological and biochemical traits related to fruit quality and yield. P. quadrangularis L. (P15) exhibited maximum flower length, fruit size, weight, juice content, shelf-life, and yield. P. edulis f. flavicarpa (P3, P5, and P2) had the highest seed count per fruit and antioxidant activity, along with greater chlorophyll and anthocyanin levels. Passiflora edulis Sims (P8 and P11) showed superior total soluble solids, carotenoids, and vitamin C. The study found that fruit shelf life positively correlated with seed weight, while the number of fruits per vine negatively correlated with seed traits and peel weight. Additionally, certain traits, such as total carotenoids, had strong positive correlations with reducing sugar and flavonoids. Principal component analysis revealed distinct trait relationships, particularly for genotypes P7 and P10. SDS-PAGE protein profiling indicated a significant distance between P3 and P14, emphasising genetic diversity. In conclusion, this research highlights the diverse morphological and biochemical characteristics of passion fruit genotypes, paving the way for the region’s improved fruit quality, yield, and breeding strategies.